Smart Jacket for Health Monitoring Using NRF Technology (International Journal of Scientific Research in Science and Technology, 2025)
The Smart Jacket for Health Monitoring utilizing Nordic Radio Frequency (NRF) technology integrates advanced wearable biosensors to enhance healthcare monitoring in hospitals, nursing homes, and remote environments. This study evaluates the reliability of vital-sign monitoring systems in extreme conditions. Key physiological parameters—including heart rate, skin temperature, core body temperature, activity level, and location—were continuously monitored in real-time with time-stamped identification for over 45 minutes. While no direct correlation was found among heart rate, activity level, and body temperature, certain periods indicated intense physical exertion. Field testing demonstrated the system's ability to effectively track both vital signs and user location in real-time. However, improvements in system reliability and robustness are necessary for broader adoption. As this technology progresses towards commercialization, its application in remote patient monitoring and routine healthcare will provide significant benefits, enabling early detection and intervention in critical health conditions.
Keywords: Health monitoring; hypothermia; bradycardia; heartbeat; NRF module; wireless communication